KINETICS OF LIDOCAINE HYDROCHLORIDE RELEASE FROM HYDROGEL MATERIALS BASED ON POLYVINYL ALCOHOL, SODIUM ALGINATE, AND HYALURONIC ACID - ІЩЕНКО, Олена; КУЧИНСЬКА, Дар’я; ОХРІМЕНКО, Ігор; СУМСЬКА, Ольга (Technologies and Engineering, 2026)
Purpose. To develop and investigate hydrogel materials based on polyvinyl alcohol, sodium alginate, and hyaluronic acid of different molecular weights as carriers for lidocaine hydrochloride in local and transdermal anesthesia systems, as well as to determine the mechanisms and kinetic parameters of active pharmaceutical ingredient release depending on the composition of the polymer matrix. Methodology. Hydrogel materials were prepared by ionotropic gelation through the interaction of alginate anionic groups (COO⁻) with Ca²⁺ ions. Rheological properties were studied using a Brookfield DV-III rotational rheometer, and the experimental data were fitted using the Ostwald–de Waele model. The release kinetics of lidocaine hydrochloride were evaluated spectrophotometrically (OPTIZEN POP UV VIS spectrophotometer, Mecasys, Republic of Korea) in phosphate buffer solution (pH 7.4) at 37 °C. Mathematical modeling of lidocaine hydrochloride release kinetics was performed using the Korsmeyer–Peppas model. Findings. The pseudoplastic behavior of all investigated systems was established (flow behavior index n = 0.38–0.52). An increase in both the concentration and molecular weight of hyaluronic acid led to a rise in viscosity (K increased from 7.21 to 14.80 Pa·s). Analysis of release kinetics using the Korsmeyer–Peppas model confirmed an anomalous diffusion mechanism for all systems (n = 0.61–0.72). For the polyvinyl alcohol/sodium alginate system at a 50/50 ratio containing 5% lidocaine, more than 50% of the active ingredient was released within 30 min, and over 80% within 90 min. Increasing the molecular weight and concentration of hyaluronic acid enabled regulation of the release profile within the range of 5–16 h. Originality. For the first time, quantitative relationships between the molecular weight and concentration (0.5 and 1.0%) of hyaluronic acid and the parameters of the Korsmeyer–Peppas model (K and n) were established for hydrogel materials based on polyvinyl alcohol, sodium alginate, and hyaluronic acid containing lidocaine. It was demonstrated that the incorporation of hyaluronic acid into the polymer matrix provides a transition from rapid drug release to a prolonged release profile and modulates the transport mechanism toward anomalous diffusion. Practical walue. The developed hydrogel materials are promising for application as wound dressings for pain relief and wound healing, transdermal patches, and ophthalmic gels. Adjustment of the composition allows targeted control of the lidocaine release profile, ranging from rapid action (5% lidocaine and 1% low-molecular-weight hyaluronic acid) to prolonged anesthesia (15% lidocaine and 1% high-molecular-weight hyaluronic acid).